Excess Liquidity and the Usefulness of the Money Multiplier - Jan Marc Berk; Jan Willem van den End (Credit and Capital Markets – Kredit und Kapital, 2022)
We model the behaviour of banks as a main driver of the changing components of the money multiplier (MM). So we provide behavioural underpinnings for the supply and demand for inside and outside money. We illustrate how the creation of large outside money balances by central banks induces behavioural changes, creating an environment characterised by a low MM and low market interest rates. The low regime reflects a state in which the functioning of the financial system changes fundamentally due to excess supply of reserves. This so-called excess liquidity trap has adverse economic consequences, is persistent, and cannot be solved by monetary policy alone. We argue that government and supervisory measures taken during the pandemic provide an example of supporting policies that are effective in escaping the excess liquidity trap.
Keywords: E51; E52; 330; monetary policy; interest rates; money multipliers